Mối quan hệ giữa cảm tính nhà đầu tư và chính sách cổ tức: Bằng chứng tại Việt Nam - Bùi Kim, Phương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This paper examines the relationship between investor sentiment and firms’ dividend policy. Using the data of listed firms on Ho Chi Minh City Stock Exchange (HSX) and Hanoi Stock Exchange (HNX) over 2009–2017 period, this paper indicates that managers do not cater to investor sentiment when making dividend payment decisions. This empirical evidence does not support the catering theory of dividends proposed by Baker and Wurgler (2004). The results remain unchanged with alternative proxies of dividend policy as well as different regression models.